Study of the physico-chemical properties of composites obtained by mechanochemical synthesis of nanoscale hydroxyapatite and synthetic zeolites - A.G. Shirokova; S.A. Bibanaeva; E.A. Bogdanova; V.M. Skachkov; O.V. Koryakova (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
In this article, the features of synthesis and physicochemical properties of a composite material based on precipitated hydroxyapatite and synthetic aluminosilicate zeolites are investigated. Using modern methods of analysis, both the obtained composite material and individual components included in its composition are certified. The material was synthesized by mixing with simultaneous grinding in a vibration mill of synthetic zeolite and hydroxyapatite, followed by annealing of the resulting mixture. The characteristics of the initial aluminosilicate zeolites and hydroxyapatite were clarified by infared spectroscopy, their interaction during mechanochemical synthesis and subsequent heat treatment of composites obtained on their basis was assessed. X-ray phase analysis of the initial synthetic zeolites indicates the loss of adsorbed and crystallization water and decomposition to complex aluminosilicate oxides of calcium and sodium during heat treatment at 1000 °C. It was also found that although precipitated hydroxyapatite is structurally unstable and its phase composition depends on temperature, the behavior of the composite material obtained on its basis differs significantly during high-temperature treatment. It was proven that thermal annealing of the composite obtained by mechanosynthesis during heat treatment at 1000 °C does not lead to chemical modification of the hydroxyapatite structure and the formation of a new compound due to the introduction of zeolite. Differential thermal analysis showed an increase in the stability of the composite material relative to its individual components. The morphology of the original materials and those subjected to heat treatment was studied using scanning electron microscopy; a change in morphology during sintering was shown. Along with the study of the thermal stability of the materials, an assessment of the linear shrinkage of the samples and their microhardness was carried out. The conducted comprehensive studies made it possible to recommend composites based on precipitated hydroxyapatite, containing 15 wt.% aluminosilicate zeolites in their composition, as promising materials for further study, possessing the best functional characteristics, including strength.